Gambaran Radiologis Artritis Inflamatori - Nathania, Liem Marcella; Ligin, Erina Damayanti (PT Kalbe Farma Tbk., 2025)
Arthritis is a common disease that often causes activity limitations. The diagnosis of inflammatory arthritis requires conventional radiography as the primary modality. Assessment of alignment (A), bone (B), cartilage loss (C), demineralization (D), erosion (E), and soft tissue swelling (S) on radiographs is necessary to differentiate the three most common inflammatory arthritides: rheumatoidarthritis, gouty arthritis, and psoriatic arthritis (PsA). Each type of arthritis has characteristic radiological features that are important for diagnosis. Rheumatoid arthritis is characterized by marginal erosion in bare areas, periarticular osteopenia, and uniform joint space narrowing with bilateral symmetrical distribution. Gouty arthritis shows punched-out erosion with overhanging edges, tophi deposits, and normal bone mineralization. Psoriatic arthritis has characteristic marginal erosions accompanied by new bone formation, pencilin- cup deformities, and dactylitis. Understanding the differences in the radiological features of these three diseases is important for establishing an accurate diagnosis and determining appropriate therapy. The combination of radiographic examination with clinical and laboratory data is expected to improve diagnostic accuracy and reduce disease progression.